Lactobacillus reuteri associado a antibióticos no tratamento da periodontite em fumantes. - Silva, Beatriz Goulart [UNESP] (Universidade Estadual Paulista (Unesp), 2020)
The present randomized controlled clinical study aimed to evaluate the influence of systemic use of Lactobacillus reuteri isolated or associated with Amoxicillin and Metronidazole, as adjunct therapies to the mechanical treatment of periodontitis in smoking patients. Inclusion and exclusion criteria made it possible to select 34 patients who were randomly allocated into groups, where patients were subjected to one of the following treatments: Group PRO (N=17), the patients were submitted to a single session of scaling and root planning (SRP), using ultrasound and manual curettes followed by systemic administration of Lactobacillus reuteri chewable tablets (2x / day / 21 days); Group ANT+PRO (N=17), the patients were submitted to a single session of SRP, using ultrasound and manual curettes, associated with systemic administration of amoxicillin (500 mg) and metronidazole (400 mg) every 8 hours, for 7 days, and after an interval of 7 days, the treatment with Lactobacillus reuteri (2x / day / 21 days) was started. Were evaluated the clinical parameters of: visible plaque index (VPI), depth on probing (DP), bleeding on probing (BP), level of clinical insertion (LCI) and gingival recession (GR), at six sites of all teeth at baseline and 90 days after SRP treatment. Data in percentage of reduction of residual pockets (DP > 4 mm) with BP were also assessed. The results of the clinical analysis revealed that at 90 days there was improvement in both groups in the parameters of BP, VPI and residual pockets compared to baseline, while in the group ANT+PRO there was also a reduction in DP and insertion gain (p<0,05). Both groups showed a reduction in DP and in the number of sites with moderate pockets. Only the group ANT+PRO showed a significant reduction in the number of deep pockets and greater reduction of DP of deep pockets at 90 days after treatment. In conclusion both adjunct therapies were effective in treatment of periodontitis in smokers, however, the combined use of Amoxicillin and Metronidazole followed by the ingestion of Lactobacillus reuteri, presented additional clinical benefits in comparation to the isolated use of Lactobacillus reuteri.

O presente estudo clínico randomizado controlado objetivou avaliar a influência do uso sistêmico de Lactobacillus reuteri isolado ou associado a Amoxicilina e Metronidazol, como terapias coadjuvantes ao tratamento mecânico da periodontite em pacientes fumantes. Critérios de inclusão e de exclusão possibilitaram a seleção de 34 pacientes que foram alocados randomicamente em dois grupos, em que os pacientes foram sujeitos a um dos seguintes tratamentos: Grupo PRO (n=17), os pacientes foram submetidos à sessão única de raspagem e alisamento radicular (RAR) utilizando-se ultrassom e curetas manuais seguida da administração sistêmica de pastilhas mastigáveis de Lactobacillus reuteri (2x/dia/21 dias); Grupo ANT+PRO (n=17), os pacientes foram submetidos à sessão única de RAR utilizando-se ultrassom e curetas manuais, associado com a administração sistêmica de amoxicilina (500 mg) e metronidazol (400 mg) a cada 8 horas, durante 7 dias e após um intervalo de 7 dias foi iniciado o tratamento com o Lactobacillus reuteri (2x/dia/21 dias). Foram avaliados os parâmetros clínicos de: índice de placa visível (IPV), Profundidade à Sondagem (PS), Sangramento à Sondagem (SS), Nível de Inserção Clínica (NIC) e Recessão gengival (RG) nos seis sítios de todos os dentes no baseline e 90 dias após tratamento. Os dados em percentagem da redução de bolsas residuais (PS > 4 mm) com SS também foram avaliados. Os resultados da análise clínica revelaram que aos 90 dias houve melhora em ambos os grupos nos parâmetros de SS, IPV e na redução de bolsas residuais quando comparado ao baseline, enquanto que no grupo ANT+PRO também foi verificada redução da PS e ganho de inserção (p<0,05). Os dois grupos demonstraram redução na PS e no número de sítios com bolsas moderadas. Somente o grupo ANT+PRO apresentou redução significante no número de bolsas profundas e maior redução de PS de bolsas profundas aos 90 dias após o tratamento. Conclui-se que ambas terapias coadjuvantes foram efetivas no tratamento da periodontite em fumantes, entretanto, o uso combinado de Amoxicilina e Metronidazol seguido da ingestão de Lactobacillus reuteri, apresentou benefícios clínicos adicionais em relação ao uso isolado de Lactobacillus reuteri.
Lactobacillus reuteri associated with antibiotics in the treatment of smokers with periodontitis.
Keywords: Periodontitis; Periodontite; Lactobacillus reuteri; Tabagismo; Antibiótico